Conscientious Objection and the Provision of Abortion at Late(r) Stages of Pregnancy - Nathan Emmerich (Canadian Journal of Bioethics)
This essay concerns a theoretical issue that has the potential to arise in the provision of late(r) term abortion in particularly liberal or highly permissive jurisdictions, meaning those that do not require criteria to be met if the procedure is to be lawful. By not establishing criteria that restrict the provision of late(r) term abortion the procedure is rendered lawful “on demand”, at least in principle. This raises the possibility that healthcare professionals may encounter specific requests for terminations that they consider morally unjustified, meaning that some might seek to “opt-out” of provision in such cases by appealing to the notion of conscientious objection. The existing literature would likely frame such appeals to be instances of selective conscientious objection. Whilst I argue that this notion is flawed, I also suggest that there is a need to recognise a degree of nuance in the ethical positions held by healthcare professionals when it comes to the provision of abortion at late(r) gestational (st)ages in jurisdictions that adopt highly permissive forms of regulation. However, given that conscientious objection should not be permitted to obstruct provision of legally permitted interventions, there is a moral imperative to ensure access, and healthcare systems must take steps to ensure provision. Whilst it may be possible, it is unlikely to be simple, and it may auger against establishing legalisation that is highly permissive.